Metabolic Screening in Psychiatric Patients: Impact of a Quality Improvement Initiative - Ghulam Murtaza (BJPsych Open, 2025)
Aims: Metabolic syndrome is highly prevalent among psychiatric rehabilitation patients, with rates ranging from 40–60% globally. The condition significantly increases the risk of cardiovascular disease and type 2 diabetes, compounded by psychotropic medications, sedentary lifestyles, and poor dietary habits. Despite established guidelines from the National Institute for Health and Care Excellence (NICE), the International Diabetes Federation (IDF), and the World Health Organization (WHO), which recommend regular metabolic screening every 6 months for patients on long-term psychotropic medications, compliance with metabolic screening in psychiatric settings remains inconsistent. This audit aimed to evaluate and improve compliance with these metabolic screening practices in psychiatric rehabilitation units through targeted interventions.